Frakcja lipidowa i białkowa nasion konopi siewnych (C. sativa L.) oraz jej korzystny wpływ na zdrowie człowieka = Lipid and protein fraction of hemp seed (C. sativa L.) and its beneficial influence on human health - Dąbrowski, Grzegorz; Skrajda, Marta Natalia (Journal of Education, Health and Sport, 2016)
Dąbrowski Grzegorz, Skrajda Marta. Frakcja lipidowa i białkowa nasion konopi siewnych (C. sativa L.) oraz jej korzystny wpływ na zdrowie człowieka = Lipid and protein fraction of hemp seed (C. sativa L.) and its beneficial influence on human health. Journal of Education, Health and Sport. 2016;6(9):357-366. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62002 http://ojs.ukw.edu.pl/index.php/johs/article/view/3839 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. FRAKCJA LIPIDOWA I BIAŁKOWA NASION KONOPI SIEWNYCH (C. SATIVA L.) ORAZ JEJ KORZYSTNY WPŁYW NA ZDROWIE CZŁOWIEKA Lipid and protein fraction of hemp seed (C. sativa L.) and its beneficial influence on human health Grzegorz Dąbrowski, Marta Skrajda* Katedra Przetwórstwa i Chemii Surowców Roślinnych Wydział Nauki o Żywności, Uniwersytet Warmińsko-Mazurski w Olsztynie *Uniwersytet Warmińsko-Mazurski w Olsztynie Katedra Przetwórstwa i Chemii Surowców Roślinnych Pl. Cieszyński 1, 10-726 Olsztyn e-mail: marta.skrajda@uwm.edu.pl Abstrakt Wprowadzenie i cel pracy: Konopie siewne wykorzystywane są od tysięcy lat do produkcji włókien oraz oleju z nasion. W ostatnim czasie nasiona tej rośliny wykorzystuje się także do produkcji izolatów i hydrolizatów białek. Celem niniejszej pracy jest opisanie składu frakcji tłuszczowej i białkowej nasion konopi siewnych oraz potencjału zdrowotnego oleju oraz izolatów i hydrolizatów białkowych pochodzących z tego surowca. Skrócony opis stanu wiedzy: Nasiona konopi są bogatym źródłem oleju oraz białka. Skład oleju jest korzystny z żywieniowego punktu widzenia z uwagi na duży udział niezbędnych nienasyconych kwasów tłuszczowych (NNKT) oraz korzystne proporcje kwasów n-6/n-3. Olej konopny zawiera także duże ilości związków bioaktywnych, takich jak fitosterole, karotenoidy, polifenole i tokoferole. Białko konopi cechuje się dobrym składem aminokwasów oraz jest źródłem bioaktywnych peptydów o działaniu antyoksydacyjnym. Podsumowanie: Ze względu na zawartość oleju o korzystnym składzie kwasów tłuszczowych i wartościowego białka, nasiona konopi powinny być coraz częściej wprowadzane do codziennej diety. Słowa kluczowe: konopie siewne, NNKT, bioaktywne peptydy, tokoferole, fitosterole, polifenole, karotenoidy Abstract Introduction and purpose: Hemp are used for thousands of years to obtain the fiber and seed oil. Recently, the hemp seeds are also used for the production of protein hydrolysates and isolates. The aim of this study is to describe the composition of the fat and protein fractions. In addition health benefits of the consumption of the oil and protein hydrolysates and isolates will be described. Brief description of the state of the knoweledge: Hemp seeds are a rich source of oil and protein. The oil composition is beneficial from a nutritional point of view due to the high content of essential fatty acids (EFAs) in the optimal ratio of n-6 / n-3. Hemp oil also contains large amounts of a bioactive compounds, such as sterols, carotenoids, polyphenols and tocopherols. Hemp protein is well balanced in terms of amino acids composition and is a source of bioactive peptides with antioxidant activity. Summary: Due to the preferred oil fatty acid composition and valuable proteins, seeds should be increasingly incorporated into the daily diet. Keywords: hemp, EFA, bioactive peptides, tocopherols, phytosterols, polyphenols, carotenoids